ARF family identification in Tamarix chinensis reveals the salt responsive expression of TcARF6 targeted by miR167 - Ye,Youju; Wang,Jianwen; Wang,Wei; Xu,Li-an (PeerJ, 2020)
Auxin response factors (ARFs) are important transcription factors (TFs) that are differentially expressed in response to various abiotic stresses. The important roles of ARFs and small RNA-ARF pathways in mediating plant growth and stress responses have emerged in several recent studies. However, no studies on the involvement of ARFs in tamarisk trees, which are resistant to salinity, have been conducted. In this study, systematic analysis revealed 12 TcARF genes belonging to five different groups in Tamarix chinensis. The microRNA response elements of miR160, which belongs to group I and miR167, which belongs to group III, were conserved in terms of their location and sequence. Moreover, digital gene expression profiles suggested that a potential miR167 target gene, TcARF6, was rapidly expressed in response to salt stress. Cloning of TcARF6 revealed that TcARF6 could be an activation TF with a glutamine-rich region and expression pattern analysis revealed that the expression of TcARF6 was significantly downregulated specifically in the roots. A significant negative correlation in the expression pattern of tch-miR167/TcARF6 indicated that this module may play a key role in the response to salt stress. Overall, these results provide basic information on the posttranscriptional regulation of TcARF6 for future investigations of the T. chinensis salt-stress response.
Keywords: Auxin response factor; MicroRNA response element; MiR167; Salt stress response